Global research profile on monkeypox-related literature (1962–2022): A bibliometric analysis - Fajar Sofyantoro; Sandro Vento; Marius Rademaker; Andri Frediansyah; Hendrix I. Kusuma (Narra Sains Indonesia, 2022)
The recent monkeypox or mpox outbreak has been a global concern. The present study evaluated the global research outputs, research trends, and topics of published research on monkeypox using a bibliometric approach. The Scopus database was searched for terms associated with